The Pengaruh Hiperrealitas Iklan terhadap Pola Konsumtif Remaja Suku Dayak Taman Sosat di Jopo, dalam terang Pemikiran Jean Baudrillard: budaya - Lorensius; Riyanto, Armada; Adon, Mathias Jebaru (Hunatech Vol. XXX, No. XXX, 2024)
The influence of advertising hyperreality on the consumptive lifestyle of Dayak Taman teenagers is an interesting phenomenon to research. In Jean Baudrillard's thinking, hyperreality refers to a condition where the representation of the real world becomes more important than the reality of authenticity itself. Advertising, as a form of representation, has a significant role in shaping consumptive lifestyles. In this study, the author analyzes how advertisements influence the consumptive behavior of Dayak Taman teenagers in Jopo Village. The author found that advertisements create images that exaggerate certain products and lifestyles. Taman Dayak teenagers who are exposed to advertisements tend to follow the consumption trends displayed in advertisements, even if it does not always match their needs. An understanding of hyperreality and Jean Baudrillard's thinking helps us understand why advertising has such a strong impact on consumptive lifestyles. This research provides insights into how advertising can influence teenagers and lead them to overconsumption. Therefore, there needs to be awareness and criticism of advertisements so that teenagers can make wiser consumption decisions.